The palliative care team in the intensive care unit - Ostgathe, Christoph; Klein, Carsten; Heckel, Maria; Hofmann, Sonja; et al. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2012)
The aim of palliative care is to relieve suffering and stabilize or improve quality of life. Prolongation of life and focus on quality of life seem to be at first glance mutually exclusive. However, in daily clinical routine they occasionally do simultaneously occur, when further medical treatment to prolong life is not successful, not appropriate, or simply refused by the patient. In general, basic competencies in palliative care should be offered by the intensive care unit teams. In complex cases, it can be reasonable to integrate a palliative care team (PCT) which can support treatment for those patients with regard to symptom-oriented therapy. They also facilitate referral of seriously ill patients to a hospice or home. Palliative care consultation is recommended, if distressing symptoms can not be alleviated sufficiently or support for referral of terminally ill patients is sought. In addition, a PCT can provide support in discussions about withdrawal of life-prolonging treatments and the aims of therapy. © 2012 Springer-Verlag.
Keywords: Communication; Palliative care; Palliative care team; Quality of life; Therapy